Victimization devices: Exploring challenges facing litigation-based transnational environmental justice - Ureta, Sebastian, Soneryd, L, and Flores, Patricio (Social and Legal Studies)
With the emergence of global mechanism for toxic harm accountability, a transnational environmental justice regime is slowly rising. One of the ways in which its taking form is through transnational litigation schemes where corporations are being locally sued by the alleged victims of their overseas misbehaviours. Using a science and technology studies approach, this article deals with one of the most central components of those schemes: victimization devices. Such concept refers to the highly varied sociotechnical assemblages through which claims about toxic victimhood are mobilized in litigation-based schemes, usually including components such as toxicological evidence and testimonies from the affected people. In order to explore the complexities involved in transnationally mobilizing these devices, this article analyses the lawsuit presented in Sweden by inhabitants of Arica, Chile, against the local mining corporation Boliden for its alleged responsibility in dumping toxic waste near their homes in the late 1980s.- Reproduced
Keywords: Arica Victims, Toxic harm, Transnational litigation, Victimisation devices, Waste